REORIENTING ASIAN DEVELOPMENT BANK POLICY TO ENHANCE FOOD SECURITY AND RURAL DEVELOPMENT - Iman Supriadi; Eva Wany (International Journal of Business, Law and Political Science, 2024)
This paper aims to evaluate the role of the ADB in rural development and food security in Asia and the Pacific and analyze the impact of its programs. The research approach involves literature analysis, case studies of ADB policy implementation, and synthesizing findings from multiple sources to develop a holistic understanding. Key findings include the success of ADB programs in improving rural infrastructure and community empowerment, as well as challenges such as implementation delays and global market uncertainty. This paper provides an in-depth look at the impact of ADB programs, presents key findings, and provides recommendations for future policy improvements